Simultaneous assessment of brain tissue oxygenation and cerebral perfusion during orthostatic stress - Krakow, Karsten; Ries, Stefan; Daffertshofer, Michael; Hennerici, Michael G. (European neurology, 2000)
Simultaneous registration of cerebral tissue oxygenation parameters obtained by near infrared spectroscopy (NIRS), intracranial blood flow velocity (CBFV) measured by transcranial Doppler sonography (TCD) and basic cardiovascular parameters was carried out during a passive 80 degrees head-up tilt table test in 15 patients with a history of orthostatic syncope and 20 control subjects. In normals, the cardiovascular parameters showed a specific course after changing to a vertical position: the heart rate increased, the mean arterial blood pressure remained unchanged, and the CBFV decreased. The NIRS measurements showed an increase in deoxyhemoglobin (HHb) and a decline in oxyhemoglobin (O(2)Hb) and the regional oxygen saturation (RSAT). Patients had a significantly more prominent decline in arterial blood pressure (p < 0.001), CBFV (p < 0.001) and RSAT (p = 0.04). Five patients experienced symptoms of (pre)syncope during the experiment, which were associated with a further sudden and marked (>10%) drop of O(2)Hb. The results indicate that the combination of TCD and NIRS increases the understanding of hemodynamic and metabolic changes during orthostatic stress, which may lead to individually suited therapeutic procedures.
Gesehen am 13.06.2022